Características da carcaça e alometria dos tecidos de cabritos F1 Boer x Saanen - Pereira Filho, José Morais; De Resende, Kleber Tomás [UNESP]; Teixeira, Izabelle Auxiliadora Molina De Almeida [UNESP]; Sobrinho, Américo Garcia Da Silva [UNESP]; Yáñez, Enrique Alejandro; Ferreira, Ângela Cristina Dias [UNESP] (FapUNIFESP (SciELO), 2008)
Thirty-five male kids Boer x Saanen kids were shaughtered at 5, 10, 15, 20 e 25 kg BW to evaluate the carcass traits and commercial cuts and tissues allometry. The diet fed to the animas was composed by cow milk in the first 49 days and ad libitum ration from the seventh day until slaughter. The cuts were obtained after cooling of the carcass and the leg dissected in muscle, bone and fat. The body weight showed a negative linear effect on cold carcass dressing and the loin-eye area/kg of carcass. The weights of leg, shoulder and neck in relation to cold carcass linearly decrease however there was a quadratic effect on ribs and loin yield. The shoulder, neck and leg showed an isometric growth (b=1) with the body, while ribs and loin was slower (b≠1). The growth of leg muscle was isometric, fat slower and faster then leg, while the subcutaneous fat was slower than the intermuscle fat. To achieve a carcass with 8 to 11 kg with superior yield of 44%, good muscle and fat proportion with lesser loss during the cooling, it is recommended to slaughter the animals weighting between 20 and 25 kg.BW. However, if the objective is to obtain carcass of slower weight, the male goat kids should be slaughtered at the end of the milking period, around 10 kg BW. © 2008 Sociedade Brasileira de Zootecnia.
Carcass traits and tissue allometry in Boer x Saanen kids
Keywords: Fat; Growth; Leg; Loin; Muscle